2011
DOI: 10.7773/cm.v37i3.1826
|View full text |Cite
|
Sign up to set email alerts
|

Validation of age determination methods and growth studies of the sand sole Pegusa lascaris (Soleidae) from the eastern-central Atlantic

Abstract: ABSTRACT. The age and growth of the sand sole Pegusa lascaris from the Canarian Archipelago were studied from 2107 fish collected between January 2005 and December 2007. To find an appropriate method for age determination, sagittal otoliths were observed by surface-reading and frontal section and the results were compared. The two methods did not differ significantly in estimated age but the surface-reading method is superior in terms of cost and time efficiency. The sand sole has a moderate life span, with ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…This demonstrated a proportional growth of the otolith with fish size, although the coefficient of determination indicated that 33.3 % of the variation in size was explained by another factor, independent from otolith size. In studies on fish growth, coefficients of determination for the relationship between otolith size and fish size have been observed to vary from 0.4 to 0.9 (Carmona & Alexandres, 1994;Quiñonez-Velázquez et al, 2002;Puentes-Ganada et al, 2004;Morales & González, 2010;Pajuelo & Lorenzo, 2011;Souza-Conceinao & Schwingel, 2011;Cerna et al, 2014). The proportionality of otolith size with fish size is very important when a retro-calculation of previous sizes has to be done, and the more precision you have, the better it is, especially because in some cases, a reabsorption of scale rings (Lee's phenomenon) can be The count of growth bands allowed to identify five age groups (0-4 years); an age-length key for O. medirastre was shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…This demonstrated a proportional growth of the otolith with fish size, although the coefficient of determination indicated that 33.3 % of the variation in size was explained by another factor, independent from otolith size. In studies on fish growth, coefficients of determination for the relationship between otolith size and fish size have been observed to vary from 0.4 to 0.9 (Carmona & Alexandres, 1994;Quiñonez-Velázquez et al, 2002;Puentes-Ganada et al, 2004;Morales & González, 2010;Pajuelo & Lorenzo, 2011;Souza-Conceinao & Schwingel, 2011;Cerna et al, 2014). The proportionality of otolith size with fish size is very important when a retro-calculation of previous sizes has to be done, and the more precision you have, the better it is, especially because in some cases, a reabsorption of scale rings (Lee's phenomenon) can be The count of growth bands allowed to identify five age groups (0-4 years); an age-length key for O. medirastre was shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Among all studies of S. cinereus published to date in which the von Bertalanffy model was utilized in one of its possible forms, estimated values of t 0 have tended to be non-zero and negative (Table 5). This suggests that the von Bertalanffy model is not capable of providing accurate descriptions of growth for this species in the earliest stages of life (Pajuelo & Lorenzo, 2011). Negative t 0 values are frequently observed for demersal fish species that experience rapid spurts of growth in the first year of life with slower rates of growth in subsequent years (Dwyer et al ., 2003; Amaral & Cabral, 2004; Teixeira et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating this should be conducted in order to ensure correct age and growth rate estimations. Such a study could be based on rearing larvae from hatching (Vigliola, 1997; Pajuelo & Lorenzo, 2011; Duffy et al , 2012; Ellender et al , 2012; Parkinson et al , 2012; Dodson et al , 2013; Farley et al , 2013).…”
Section: Discussionmentioning
confidence: 99%